Graphitic carbon nitrides as platforms for single-atom photocatalysis. (11th December 2020) - Colombari, Felippe M.; da Silva, Marcos A. R.; Homsi, Mauricio S.; de Souza, Beatriz R. L.; Araujo, Milenny; Francisco, Juliana L.; da Silva, Gelson T. S. T.; Silva, Ingrid F.; de Moura, André F.; Teixeira, Ivo F.
Abstract : Adding single metal atoms to graphitic carbon nitrides alters their properties, impacting their use in photocatalysis. Abstract : Herein we demonstrate that adding single atoms of selected transition metals to graphitic carbon nitrides allows the tailoring of the electronic and chemical properties of these 2D nanomaterials, directly impacting their usage in photocatalysis. These single-atom photocatalysts were successfully prepared with Ni 2+, Pt 2+ or Ru 3+ by cation exchange, using poly(heptazine imides) (PHI) as the 2D layered platform. Differences in photocatalytic performance for these metals were assessed using rhodamine-B (RhB) and methyl orange (MO) as model compounds for degradation. We have demonstrated that single atoms may either improve or impair the degradation of RhB and MO, depending on the proper matching of the net charge of these molecules and the surface potential of the catalyst, which in turn is responsive to the metal incorporated into the PHI nanostructures. Computer simulations demonstrated that even one transition metal cation caused dramatic changes in the electronic structure of PHI, especially regarding light absorption, which was extended all along the visible up to the near IR region. Besides introducing new quantum states, the metal atoms strongly polarized the molecular orbitals across the PHI and electrostatic fields arising from the electronic transitions became at least tenfold stronger. This simple proof of concept demonstrates that these new materials hold promise as tools for many important photocatalytic reactions that are strongly dependent on our ability to control surface charge and its polarization under illumination, such as H2 evolution, CO2 reduction and photooxidation in general.